Dow Chemical Company plant in Midland, Michigan - Dow Chemical Company (1900)
General view, taken from the Tittabawassee Riverfront opposite George Street, of the Dow Chemical Company facilities in Midland, Michigan following the completion of Plant E.
Keywords: Industries; Dow Chemical Company; Michigan--Tittabawassee River